A study on Select Solar Cell’s Voltage Output at High Altitudes Using a Weather Balloon - Nawash, Jalal M.; Holzer, Rebecca; Taylor, Rebekah; Bogeuschuetz, Jacob (Proceedings of the Wisconsin Space Conference, 2015)
The Voltage output of select solar cells was monitored as a function of altitude up to approximately 93,000 feet. A weather balloon was used to carry the solar cells to the required altitude. Two launches were accomplished to acquire data for analysis. Data collected also included the altitude, temperature and pressure. The voltage signal of the used solar cells depended largely on temperature. It was discovered that the voltage signal of the solar cells has a complex relationship with altitude. Temperature had a significant influence on the magnitude of the voltage signal at lower altitudes, but this influence may have declined at higher altitudes.